Integrated Community-Based Maternal Health Promotion to Improve Knowledge of Pregnancy, Breastfeeding, and Mental Health - Suci Anggraeni; Nur Yeni Hidajaturrokhmah; Yenny Puspitasari; Lingga Kusuma Wardani; Reni Nurhidayah (Universitas STRADA Indonesia, 2026)
Maternal and child health problems remain a major public health concern, particularly in developing countries, where maternal complications, suboptimal breastfeeding practices, and unrecognized maternal mental health issues contribute to adverse outcomes. This study highlights the novelty of an integrated community-based maternal health promotion approach that combines physical health education, practical skill development, and maternal mental health components. This community service aimed to improve knowledge of pregnancy danger signs, exclusive breastfeeding practices, and maternal mental health in Rejomulyo Village, Kediri.This study employed a community-based participatory approach using a pre-experimental one-group pretest–posttest design involving 52 participants, including pregnant women, breastfeeding mothers, and family members. The intervention included health education, interactive discussions, demonstrations of breastfeeding techniques, and maternal mental health assessment using the Edinburgh Postnatal Depression Scale (EPDS). Data were collected through pre–post assessments and analyzed using descriptive and comparative approaches.The results showed a significant improvement in participants’ knowledge. Knowledge of pregnancy danger signs increased from 45.0% to 85.0%, understanding of early detection from 40.0% to 80.0%, knowledge of exclusive breastfeeding from 50.0% to 88.0%, and understanding of breastfeeding techniques from 42.0% to 82.0%. In addition, maternal mental health assessment showed an improvement in participants’ psychological condition, as indicated by a decrease in mean EPDS scores from 10.2 ± 3.1 to 6.8 ± 2.7, along with a reduction in the proportion of participants at risk of depressive symptoms from 46.2% to 21.1% after the intervention.In conclusion, the integrated approach combining health education, practical skills, and maternal mental health components is effective in improving maternal knowledge and engagement. This model offers a comprehensive and scalable strategy for enhancing maternal and child health outcomes in community settings.